The Effects of Ultra-high Pressure Treatment on the Phenolic Composition of Red Wine - Chen, X.; Li, L.; You, Y.; Mao, B.; Zhao, W.; Zhan, J. (South African Journal of Enology and Viticulture, 2016)
Wine is usually aged in oak barrels. In this study, young red wines were treated with ultra-high pressure (UHP) to stimulate the ageing process. Changes in phenolic acids, flavan-3-ols and proanthocyanidins were determined by reverse-phase high pressure liquid chromatography (RP-HPLC). The concentration of phenolic acids increased, while the levels of flavan-3-ols decreased. The content and structure of proanthocyanidins also changed and the tendency was similar to that of natural ageing.